Competitive Implications of Interfirm Mobility - Wezel, Filippo Carlo; Cattani, Gino; Pennings, Johannes M. (Organization Science, 2006)
This paper examines the competitive consequences of interfirm mobility. Because the loss of key members (defined as top decision makers) to competing firms may amount to a replication of a firm’s higher-order routines, we investigate the conditions under which interfirm mobility triggers transfer of routines across organizational boundaries. We examine membership lists pertinent to the Dutch accounting industry to study key member exits and firm dissolutions over the period 1880–1986. We exploit information on the type of membership migration (individual versus collective) and the competitive saliency of the destination firm as inferred from the recipient status (incumbent versus start-up) and its geographic location (same versus different province). The dissolution risk is highest when collective interfirm mobility results in a new venture within the same geographic area. The theoretical implications of this study are discussed.